Cash Flow at Risk of the Retailers in UK - WU, JIE (2013)
Risk management is an important activity of financial or non-financial firms. There is a significant amount of material helping the financial firms to measure risk, but for non-financial firms, it seems that they not receive too much attention to measure their risk. The aim of this dissertation was to use CFaR model that could be measured by top-down approach and exposure-based CFaR model to predict the cash flow shortfall of the firms. In this paper, EBITDA of the non-financial firms would be regarded as cash flow. The percentages of cash flow shortfall in two approaches would be compared with each other. Most of the firms show the consistent results when the two approaches are compared that could help the management to make the efficient decisions although there are some limitations in the two approaches. But for the firms whose results of CFaR are not consistent in two approaches, the other factors or something that is not reasonable in methods should be taken into account. Finally, other financial indicators also could be used as cash flow instead of EBITDA to help firms make wise decisions.